Towards a typology of "environmentally-adjusted" national sustainability indicators: Key concepts and policy application - Martin O'Connor (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper first describes two types of adjustments to National Accounting Systems, which take the environment into account: the first type centres on accounting conventions, through a change in the system boundary, in order to include specified categories of environmental assets (called "Aggregate Indicator of the Change, during the Current Year, in the Economic Assets of the Nation" AICCAN); the second one is based on hypotheses of adjustment of the economy itself, that is an 'adjusted economy' with new patterns of production processes, levels of production and consumption activities, etc (called "Greened Economy GDP" GeGDP). It then explains how the two types of indicators address these different roles of natural capital respectively and, as such, respond to distinct policy questions. Finally, issues relating to the degree of openness of the national economy and the national territory to the rest of the world, as well as to the contribution of social and community capital to societal welfare are raised.
Keywords: Q2; Q3; O47; 330; Green national accounting; environmentally-adjusted aggregates; cost effectiveness; sustainability; Umweltökonomische Gesamtrechnung; Nachhaltige Entwicklung; Wirtschaftsindikator; Welt